2008
DOI: 10.1111/j.1365-2486.2008.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends in streamflow from semiarid rangelands: uncovering drivers of change

Abstract: In the last 100 years or so, desertification, degradation, and woody plant encroachment have altered huge tracts of semiarid rangelands. It is expected that the changes thus brought about significantly affect water balance in these regions; and in fact, at the headwater-catchment and smaller scales, such effects are reasonably well documented. For larger scales, however, there is surprisingly little documentation of hydrological change. In this paper, we evaluate the extent to which streamflow from large range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 45 publications
2
51
0
Order By: Relevance
“…However, whether or not any increases in evapotranspiration are discernable at the watershed scale will also depend on the proportion of the watershed affected by encroachment. The present study concurs with past work in suggesting that while woody encroachment can increase evapotranspiration significantly, those increases are strongly dependent on the degree to which the site was degraded prior to woody encroachment (Wilcox et al 2008).…”
Section: Resultssupporting
confidence: 92%
“…However, whether or not any increases in evapotranspiration are discernable at the watershed scale will also depend on the proportion of the watershed affected by encroachment. The present study concurs with past work in suggesting that while woody encroachment can increase evapotranspiration significantly, those increases are strongly dependent on the degree to which the site was degraded prior to woody encroachment (Wilcox et al 2008).…”
Section: Resultssupporting
confidence: 92%
“…The trends were determined by applying the BS-MK and Sen tests to the annual and daily series of streamflow series. Incremental percentiles on an annual basis were used to obtain data series [44]. The observed data from each year were sorted in descending order.…”
Section: Trends and Change Point Analysismentioning
confidence: 99%
“…In the Southern Great Plains, researchers reported increasing trends in baseflow with tree cover increased (Wine and Zou, 2012). Wilcox et al (2008b) also showed that increased baseflow, in central Texas watersheds, was attributable to deeply rooted trees and greater infiltration capacity of soils as degraded grasslands were converted to woodlands. A strip of forest, grassland, and shrubland is also observable in the Ozark Plateaus in Missouri, downstream of the basin, leading to relatively elevated baseflow yield ( Fig.…”
Section: Mean Variability and Spatial Distribution Of Baseflowmentioning
confidence: 99%